Electrophysiological recordings of juxtacellularly labelled striatal interneurons in vivo - Sharott, A; Doig, N; Garas, F; Vinciati, F; Magill, P (University of Oxford, 2019)
Each MATLAB .mat file contains an electrophysiological recording of a single striatal interneuron and coincident electrocorticogram (ECoG). Neurons are only included in this data set if they were juxtacellularly labelled following recording, recovered post-mortem and confirmed to express either parvalbumin (PV), choline acetyl transferase (ChAT), nitric oxide synthase (NOS) or calretinin (CR).